1998
DOI: 10.1023/a:1009732511707
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Logically a relation is expected between time spent on individual study and achievement. The purpose of this study is to examine whether a positive relation exists between the amount of time spent on individual study and academic achievement and whether this differs when using a test measuring short-term knowledge or one measuring long-term knowledge. Data were collected in a problem-based medical curriculum. The results suggest that time spent on individual study correlates poorly with scores on the test meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…These findings support Van der Huk et al who showed large individual variation in the time spent on self-study for each module in a problem-based curriculum [6]. It is encouraging to compare our figures with those of Snelling et al because together they suggest that effective self-study is not just a matter of time available, but depends on students taking responsibility for their own learning [2].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings support Van der Huk et al who showed large individual variation in the time spent on self-study for each module in a problem-based curriculum [6]. It is encouraging to compare our figures with those of Snelling et al because together they suggest that effective self-study is not just a matter of time available, but depends on students taking responsibility for their own learning [2].…”
Section: Discussionsupporting
confidence: 86%
“…For example, factors such as difficulty of the scientific area, field of study, number of assessments and different supervised learning environments are considered to be associated with time devoted to self-study [611]. Conversely, students differ in the time they need to achieve learning outcomes, which can be explained by individual characteristics and learning styles [6, 12–16]. For medical students, self-learning experiences and time for self-study will allow them to develop skills for lifelong learning.…”
Section: Introductionmentioning
confidence: 99%
“…The most common method is student reporting, at the end of the course or semester or on two/three times occasions during the course, indicating the average hours per week that they devoted to study (Dolmans, Wolfhagen, Essed, Scherpbier, & Van Der Vleuten, 2001;Guillaume & Khachikian, 2011;Pogacnik et al, 2004;Van den Hurk, Wolfhagen, Dolmans, & Van der Vleuten, 1998). A possible limitation of using this method is the risk of students' over-or underestimating study hours because it's difficult for students to retrospectively remember the time that they spent studying.…”
Section: Self-report Methods Of Self-studymentioning
confidence: 99%
“…The self-study phase (i.e., step 6 in the Seven-Jump) has been a particularly troublesome aspect of the PBL cycle , which in addition has been difficult to study, as it mostly takes place individually, outside of the tutorial group. The amount of time students spend on self-study is not necessarily related to their academic achievement (Kamp, Dolmans, Van Berkel, & Schmidt, 2012;Van den Hurk, Wolfhagen, Dolmans, & Van der Vleuten, 1998), indicating that during this time spent on self-study, students might be using an ineffective approach to learning. Therefore, rather than putting emphasis on the time students spend studying, it might be more important to focus on the use of effective learning strategies.…”
Section: Promoting and Measuring Srl In Pblmentioning
confidence: 99%
“…Theoretically, one would assume that study time and self-regulation are important factors in explaining academic achievement. However, research has shown that time spent on selfstudy is not necessarily related to higher academic achievement (Kamp, Dolmans, Van Berkel, & Schmidt, 2012;Van den Hurk, Wolfhagen, Dolmans, & Van der Vleuten, 1998). Therefore, it might be more important to emphasize effective learning during self-study, rather than emphasizing the time spent on learning.…”
Section: Introductionmentioning
confidence: 99%